Dampak Hutang Terhadap Manajemen Laba dengan Tata Kelola sebagai Variabel Moderasi Pada Bank Terdaftar Di BEI - Septo Aji, Arwinto (Akademi Akuntasi Effendiharahap, 2022)
This research aimed to analyze the influence of leverage to earnings management and the ability to analyze the influence corporate governance consisting of institusional ownership, managerial ownership, audit quality, and independent commisioner in influencing earnings managemen on the listed manufacturing companies spesifically consumer goods in Indonesia Stock Exchange during years 2014-2016. In this research, there were one dependent variables, one independent variables, and four moderating variables. The dependent variable in this study is earnings management. The independent variable of this study is leverage. Independent variable in this study is leverage. Moderating variable in this study consists of institutional ownership, managerial ownership, quality audits, and independent board. The results showed that leverage significantly influence to earnings management. Moderating variables that influence the relationship of leverage to earnings management is institutional ownership. Meanwhile managerial ownership, the proportion of independent board and audit quality is not moderating variables